EFEKTIVITAS KEBIJAKAN DANA DESA BAGI PEMBANGUNAN EKONOMI PEDESAAN DI KECAMATAN HARIAN KABUPATEN SAMOSIR - Pawer Darasa Panjaitan; Darwin Damanik (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine whether the use of village funds was effective in developing the rural economy and infrastructure development in Harian District, Samosir Regency. Qualitative research methods were used in this study, while the data analysis techniques used were descriptive qualitative data analysis techniques. The results obtained by respondents stated that village funds distributed from the government were sufficient for village development, the existence of village funds was very helpful for village development, the largest use of village funds was used for the construction and maintenance of farm roads, and in community empowerment the village funds were mostly used for village government programs for village community empowerment, the village government compiles planning documents, each planning program must be supported by the village community, in the implementation the village government informs every expenditure and income of funds through banners and placed in front of the village head office.